Підготовка майбутніх фахівців соціальної сфери до роботи з соціально дезадаптованими дітьми - Гунько, Степан; Hunko, Stepan (Східноєвропейський національний університет імені Лесі Українки, 2017)
У статті розкриваються сучасні наукові підходи до підготовки майбутніх фахівців соціальної сфери до роботи з соціально дезадаптованими дітьми, які передбачають або орієнтацію на модель надання допомоги дітям цієї категорії, яка буде використовуватися фахівцем у професійній діяльності або спрямованість на формування в нього готовності до роботи з даною категорією дітей, де готовність виступає як результат фахової підготовки. Обґрунтовується необхідність наявності в майбутніх фахівців соціальної сфери системи знань про особливості соціальної дезадаптації, її чинники, види, форми, прояви, умінь здійснювати роботу з такою категорією дітей та сформованих на належному рівні особистісних якостей, що дозволить фахівцеві проводити ефективну соціально-педагогічну роботу з соціально дезадаптованими дітьми. Accumulation the social different problems are lead to the appearance and development of negative effects them in social life, one of social problems is social disadaptation of children. To provide effective social and educational support for children in this category can only specialist who has extensive knowledge of the essence and causes of social disadaptation and to use skills of specific forms and methods of social and educational work and professional partnership between all actors of social upbringing, which seeks to professional development, self-development and self-realization. In the article discussed modern scientific approaches to training future experts of social sphere and in particular to work with socially maladaptive children. Was substantiated that most productive way such preparation is formation at the student preparedness for such activity. A combination of knowledge about the features of social disadaptation its factors, types, forms, signs, skills to perform work with this category of children and formed at the appropriate level of personal qualities allowed specialist carry out effective work with socially maladaptive children. Analysis of results diagnosis of the condition training future social workers for working with this category of children was shown that they have some level of knowledge about essence and causes of social disadaptation of children but this knowledge are fragmented and unstructured. Students are not formed professional and pedagogical quality and they need development of empathy, civic responsibility, communicative tolerance, verbal creativity, the ability to accept other, stress tolerance, ability to self-control. Conclusions are that the state of training of future social workers not allow them in future to carry out effective work that to solve problems with socially maladaptive children.
Training of future professionals for social work with socially maladaptive children
Keywords: соціальна дезадаптація; social disadaptation; професійна підготовка; професійно-педагогічні якості; professional training; professional and pedagogical quality